New Blood: The Promise of Environmental Health Citizen Science Projects. - Averett, Nancy (Environmental Health Perspectives, 2017)
The article discusses U.S. community involvement of citizen scientists in environmental cleanup and protection, under guidance of the U.S. Environmental Protection Agency (EPA). An overview of the citizens' roles in environmental cleanup of Superfund sites in the U.S., including assistant professor Mónica Ramírez-Andreotta's role in this regard, is provided.